Improve Customer Satisfaction through Product Innovation in Social Media - Prasetya Tri Mahendra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to identify and explain the importance of product innovation on consumer satisfaction through social media at HK Food Service Company, Nganjuk. This type of research uses quantitative research methods with a causal associative research design. In determining the sample, researchers used 73 consumers. Data analysis used validity test, reliability test, and classical assumption test, with data collection techniques in the form of an online questionnaire. Hypothesis testing by performing t statistical test for partial testing. The results of the study concluded that product innovation has a partial effect on customer satisfaction, as evidenced by the acquisition of the t value of 2.934 is greater than the t table with a significance of less than 0.05.